SOFTWARE PROJECT MANAGEMENT - YADAV, RONIT; SOLANKI, SACHIN; ARORA, SAHIB (IJRDO -Journal of Computer Science Engineering, 2015)
Software project management is the art and science of planning and leading software projects. It is a sub-discipline of project management in which software projects are planned, implemented, monitored and controlled